Analisis Peran Affiliate Marketing dan Live Streaming terhadap Keputusan Pembelian Produk di Shopee - Febbie Rosiana Dewi; Munawaroh Munawaroh (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Digital transformation and e-commerce have changed consumer behavior in purchasing products. This research aims to analyze the role of Affiliate Marketing and Live Streaming on purchasing decisions. This research uses a qualitative approach with a descriptive-analytic method, which focuses on analyzing the role of Affiliate Marketing and Live Streaming in product purchasing decisions on the Shopee e-commerce platform. This research takes an analytical approach based on a literature review, analyzing the role of affiliate marketing and live streaming in influencing product purchasing decisions on the Shopee e-commerce platform. The results of this research show that affiliate marketing plays a role in purchasing decisions, as well as live streaming has a role in shopee purchasing decisions because according to the results of analysis from several sources and journals, both have an influence on purchasing decisions.